Islamic Spiritual Intelligence to Resilience at Work: A Moderated Mediation Model - Veina Ayu Restiani; Nafia Ilhama Qurratu'aini (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2025)
Introduction: Employees certainly cannot be separated from internal and external conflicts that can affect their behavior at work, this research will discuss Islamic spiritual intelligence on resilience at work as an employee's ability to manage conflicts to create positive behavior, with the moderating influence of OCB and toxic environment as mediation. Methods: This research uses quantitative methods with purposive sampling techniques and the Slovin formula in determining the sample so that 400 respondents are obtained, then analyzed using SmartPLS 4.0 to answer the research hypothesis. Results: The results of this research found a positive and significant effect of Islamic spiritual intelligence on OCB, a positive and significant effect of OCB on resilience in the workplace, and a negative and insignificant effect of OCB on resilience in the workplace moderated by toxic environment, that Islamic spiritual intelligence in employees can increase resilience by reducing emotional exhaustion and as a result there is positive energy shown by OCB behavior. Conclusion and suggestion: The findings of this research indicate that the behavior displayed by individuals in the workplace has a supporting factor, namely Islamic spiritual intelligence, thus, employees can understand that having Islamic spiritual intelligence will be better at managing behavior because they act according to inner beliefs, can regulate emotions in themselves so that resilience is formed in employees, and have a desire to be useful and sincere in doing work so that positif behavior is formed.